Matching violins in terms of timbral features - Łukasik, Ewa (Archives of Acoustics, 2006)
In the paper an attempt to match musical instruments in terms of timbral features of their sound is made for a collection of 53 high quality concert violins. The starting point of the analysis is calculation of a set of features based on harmonic analysis, e.g. odd-to-even harmonics amplitudes ratio, intensity of the first and higher harmonics etc., and a set of linguistic descriptors of violin timbre related to these features. The semantically disjoint categories of timbre characteristics are considered. The result of the analysis is the allocation of instruments to those semantic categories with the expectation of the discovery of their similarities in individual timbre dimensions. Although evident matching did not occur, certain possibilities of uncovering expert preferences have been noticed. The outcome of the research provides supportive cue for the design of a method of inferring preference models from the objective characteristics of musical sounds.